2004
DOI: 10.1073/pnas.0404006101
|View full text |Cite|
|
Sign up to set email alerts
|

Feline immunodeficiency virus targets activated CD4 + T cells by using CD134 as a binding receptor

Abstract: The major surface glycoprotein of feline immunodeficiency virus (FIV) specifically binds to a 43-kDa glycoprotein expressed on the surface of a subset of T cells in peripheral blood mononuclear cells and IL-2-dependent T cell lines. Binding to this molecule, in conjunction with CXC chemokine receptor (CXCR) 4, is required for productive infection of these cells by primary isolates of FIV. Here, we demonstrate that the 43-kDa molecule is CD134, a receptor for FIV recently identified independently [Shimojima, M.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
125
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(133 citation statements)
references
References 31 publications
7
125
1
Order By: Relevance
“…Persistent immune activation in HIV and FIV infection results in progression to AIDS [6,8,23]. Recent studies reported that FIV targets activated CD4+ cells using its primary receptor upregulated by stimuli and cytokines, indicating the infection is propagated in activated and proliferating T cells preferentially [4,14,22]. Additionally, lasting activation of immune cells leads to an anergic state of the cells and a lack of sensitivity to immune response including failures of cytokine production, antigen recognition and transmission of signaling pathways [12,16].…”
mentioning
confidence: 99%
“…Persistent immune activation in HIV and FIV infection results in progression to AIDS [6,8,23]. Recent studies reported that FIV targets activated CD4+ cells using its primary receptor upregulated by stimuli and cytokines, indicating the infection is propagated in activated and proliferating T cells preferentially [4,14,22]. Additionally, lasting activation of immune cells leads to an anergic state of the cells and a lack of sensitivity to immune response including failures of cytokine production, antigen recognition and transmission of signaling pathways [12,16].…”
mentioning
confidence: 99%
“…Interestingly, ELR1 is a member of the TNFR protein family, and TNFR-like proteins have been identified as receptors for certain avian oncoviruses and as a co-receptor component (CD134) for FIV (Brojatsch et al, 1996;Adkins et al, 1997Adkins et al, , 2000de Parseval et al, 2004;Shimojima et al, 2004;Zhang et al, 2005;Barnard et al, 2006). Taken together, these observations suggest that EIAV may represent a critical transitional link between the simple oncoviruses and the more complex immunodeficiency lentiviruses in terms of genetic composition and receptor usage.…”
Section: Discussionmentioning
confidence: 53%
“…The SU protein is bound at the virion surface through interaction with the TM protein and is responsible for the initial binding to receptor proteins on the target cell surface. Studies of the specificity of functional receptors for various retroviruses have indicated a general pattern of single receptor protein use by oncoviruses (such as murine and avian leukemia viruses) that is in distinct contrast to the dual co-receptor usage observed with the lentiviruses human immunodeficiency virus (HIV), simian immunodeficiency virus (SIV) and feline immunodeficiency virus (FIV) (Eiden et al, 1993;de Parseval et al, 2004;Douglas et al, 1997;Barnard et al, 2006). Whilst the general assumption has been that all lentiviruses may use dual co-receptors for infection of target cells, the recent identification of a single functional receptor for equine infectious anemia virus (EIAV) has revealed an unexpected diversity in lentivirus receptor specificity and interactions .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been conflicting reports regarding the pathogenicity of lentiviruses in nondomestic felids, and the observation that two distinct biological phenotypes can be discerned between subtypes B and E of FIV Ple may indicate distinct pathogenicities in vivo. The virus-receptor interaction is a critical determinant of viral cell tropism and cytopathicity, and FIV Fca targets activated CD4 ϩ T cells primarily due to the restricted expression of the primary receptor CD134 and coreceptor CXCR4 in this T-cell compartment (12,34,49). Accordingly, a decline in circulating CD4 ϩ T lymphocytes is associated with FIV infection of the domestic cat (1).…”
mentioning
confidence: 99%